Antibacterial and cytotoxic activities of the Syzygium polyanthum leaf extract from Malaysia - Nordin, Muhammad Luqman; Othman, Abdul Aziz; Abdul Kadir, Arifah; Shaari, Rumaizi; Osman, Abdinasir Yusuf; Mohamed, Maizan (Veterinary World, 2019)
Background and aim: The increasing prevalence of drug resistance eventually leads scientist to discover new drugs that could solve the problem. Since ancient immemorial times, medicinal plants generally known as herbs were widely used in every culture throughout the world. In fact, currently up to 70,000 plant species have been screened for biological activities and about 70% ends up for commercialization. Therefore, this study was aimed to evaluate the potential cytotoxic and antibacterial effect of Syzygium polyanthum leaves which are local Malaysia plants, against 4T1 and MCF-7 mammary carcinoma cells, respectively, and also against bacteria causing mastitis in cows. Materials and methods: The cytotoxic effect of hydromethanolic extract of S. polyanthum against 4T1 and MCF-7 mammary carcinoma cells was evaluated using 3-(4, 5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay. The cells were treated with the concentration of extracts ranging from 15.63 µg/mL to 1000 µg/ml for 72 h, and the percentage of cell survivability was determined based on minimum concentration that was able to allow at least 50% growth of cancer cells (IC50) after 72 h. The antibacterial activity was tested against common bacteria causing mastitis in cow. The bacteria were isolated from milk samples. The antibacterial activity of the extract was determined by disk diffusion method and susceptibility test based on minimum inhibitory concentration (MIC). Results: Staphylococcus aureus, Staphylococcus hyicus, and Staphylococcus intermedius were isolated from the milk samples that positive for mastitis. The MIC values range from 7.12 mm to 13.5 mm. The extract exhibits the widest zone of inhibition (13.5±0.20 mm) at 1000 mg/ml of concentrations. The extract relatively has low cytotoxicity effect against 4T1 and MCF-7 cells with IC50 values ranging from 672.57±59.42 and 126.05±50.89 µg/ml, respectively. Conclusion: S. polyanthum exerts weak antibacterial activity and cytotoxic effect to mammary carcinoma cells. The extract does not toxic to cells. However, further study is recommended, especially, this plant should be tested for in vivo.